Twenty bone-mineral-density loci identified by large-scale meta-analysis of genome-wide association studies - RIVADENEIRA, Fernando; STYRKARSDOTTIR, Unnur; CUPPLES, L. Adrienne; DELOUKAS, Panagiotis; DEMISSIE, Serkalem; GRUNDBERG, Elin; HOFMAN, Albert; KONG, Augustine; KARASIK, David; VAN MEURS, Joyce B; OOSTRA, Ben; PASTINEN, Tomi; et al. (Nature genetics, 2009)
Fernando Rivadeneira and colleagues report findings from a large-scale meta-analysis of genome-wide association studies for bone mineral density. The loci identified in this study map to genes in signaling pathways relevant to bone metabolism and highlight the complex genetic architecture underlying osteoporosis. Bone mineral density (BMD) is a heritable complex trait used in the clinical diagnosis of osteoporosis and the assessment of fracture risk. We performed meta-analysis of five genome-wide association studies of femoral neck and lumbar spine BMD in 19,195 subjects of Northern European descent. We identified 20 BMD loci that reached genome-wide significance (GWS; P < 5 × 10 −8 ), of which 13 map to regions not previously associated with this trait: 1p31.3 ( GPR177 ), 2p21 ( SPTBN1 ), 3p22 ( CTNNB1 ), 4q21.1 ( MEPE ), 5q14 ( MEF2C ), 7p14 ( STARD3NL ), 7q21.3 ( FLJ42280 ), 11p11.2 ( LRP4 , ARHGAP1 , F2 ), 11p14.1 ( DCDC5 ), 11p15 ( SOX6 ), 16q24 ( FOXL1 ), 17q21 ( HDAC5 ) and 17q12 ( CRHR1 ). The meta-analysis also confirmed at GWS level seven known BMD loci on 1p36 ( ZBTB40 ), 6q25 ( ESR1 ), 8q24 ( TNFRSF11B ), 11q13.4 ( LRP5 ), 12q13 ( SP7 ), 13q14 ( TNFSF11 ) and 18q21 ( TNFRSF11A ). The many SNPs associated with BMD map to genes in signaling pathways with relevance to bone metabolism and highlight the complex genetic architecture that underlies osteoporosis and variation in BMD.